PROBLEMS OF ENGLISH LEXICOGRAPHY (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
The article “Problems of English Lexicography” examines the key challenges faced by lexicographers in the compilation and development of English dictionaries. It explores issues such as the dynamic nature of the English language, including the integration of neologisms, loanwords, and slang.The article addresses the difficulties of representing regional and global varieties of English, such as British, American, and World English, while maintaining standardization. It also highlights the complexities of semantic ambiguity, polysemy, and idiomatic expressions in definition formulation. Furthermore, the role of technological advancements, including computational tools and digital corpora, is discussed in relation to improving the efficiency and accuracy of lexicographic work. The study provides insights into balancing linguistic precision, cultural sensitivity, and user accessibility in modern English lexicography